The Interactional Impact of Defence Expenditure and Arms Importation on Economic Growth in Nigeria: An Autoregressive Approach - Muhammed Umar Aminu; Abu Sufian Abu Bakar (International Journal of Economics and Financial Issues, 2016)
Little is done on the empirical analyses of the impact of defence expenditure on arms and economic growth. The few conducted concentrated on developed countries, which are exporters of arms. This study examines the short run and long run impact of arms importation on the economic growth in Nigeria, using ARDL model. Literature on defence expenditure and economic growth are often conflicting and inconclusive. These outcomes are due to the non-linear growth effects of defence and incorrect model specifications. The crucial growth effects of defence expenditure can be traced by properly controlling the interaction term. This paper examines the defence-arms interaction on Nigeria in the context of Aizeiman and Glick (2006) models. The result reveals that defence-arms interaction in Nigeria exerts negatively on the economic growth. It therefore recommends that defence R&D as well Defence Industrial Cooperation of Nigeria (DICON) should be properly financed and managed for efficiency and self-reliability.